Shoulder pain due to tennis injury - Peicha, G. (1997)
The main reason for shoulder problems in tennis athletes is overuse of the sub-acromial tissue and a subsequent impingement caused by the combination of the complex movement elevation - abduction - external rotation. The result is a chronic inflammatory reaction. The second important reason is instability caused by fatigue of the rotator cuff, followed by a mild anterior translocation of the humeral head. It is very important to differentiate between primary and secondary impingement. The `relocation test' is the best way to do this. An exact, standardized clinical evaluation is the basis for a clear diagnosis for shoulder pain, and the key to successful treatment. Systematic clinical assessment starts with a detailed patient history, followed by evaluation of the active range of motion of the shoulder. Rotator cuff tests are then performed, followed by testing of joint stability. Examination is completed by standard X-rays and ultrasound, CT or MRI if necessary.